Human Exposure to Pesticides in Dust from Two Agricultural Sites in South Africa - Degrendele, Céline; Prokeš, Roman; Šenk, Petr; Jílková, Simona Rozárka; Kohoutek, Jiří; Melymuk, Lisa; Přibylová, Petra; Dalvie, Mohamed Aqiel; Röösli, Martin; Klánová, Jana; Fuhrimann, Samuel (Toxics, 2022)
Over the last decades, concern has arisen worldwide about the negative impacts of pesticides on the environment and human health. Exposure via dust ingestion is important for many chemicals but poorly characterized for pesticides, particularly in Africa. We investigated the spatial and temporal variations of 30 pesticides in dust and estimated the human exposure via dust ingestion, which was compared to inhalation and soil ingestion. Indoor dust samples were collected from thirty-eight households and two schools located in two agricultural regions in South Africa and were analyzed using high-performance liquid chromatography coupled to tandem mass spectrometry. We found 10 pesticides in dust, with chlorpyrifos, terbuthylazine, carbaryl, diazinon, carbendazim, and tebuconazole quantified in >50% of the samples. Over seven days, no significant temporal variations in the dust levels of individual pesticides were found. Significant spatial variations were observed for some pesticides, highlighting the importance of proximity to agricultural fields or of indoor pesticide use. For five out of the nineteen pesticides quantified in dust, air, or soil (i.e., carbendazim, chlorpyrifos, diazinon, diuron and propiconazole), human intake via dust ingestion was important (>10%) compared to inhalation or soil ingestion. Dust ingestion should therefore be considered in future human exposure assessment to pesticides.
Keywords: plant protection products; Africa; intake dose; agriculture; residential exposure; temporal variations; spatial variations; exposure pathway